Real Time Suppression of Howling Noise in Public Address System. (2016) - Jithin, T.; Salih, K.K. Mohamed; Jayan, A.R.
Abstract: Howling noise is a common phenomenon in a public address system. It is built up due to the acoustic coupling between the speaker system and the microphone when it creates a positive feedback. Real time implementation of howling noise detection and suppression was implemented using TMS320C6713 DSK starter kit. The whole implementation was done based on direct memory access (DMA) feature of the DSP processor. The method uses the properties of howling noise for efficient detection and has the advantage of suppressing the noise. Howling detection is performed based on spectral flatness measure (SFM) of each input speech frame. For frames without howling, the input is passed as such to the output. Howling suppression is performed by making output samples as zero if the presence of howling noise is detected.